Social networks in China - Che, Xianhui; Ip, Barry (Chandos social media series., 2018)
Social Networks in China provides an in-depth guide to Chinese social networks, covering behaviors, usage, key issues, and future developments. Chinese scholarship and cultural idiosyncrasies in technology remain a relatively under-researched area. While such issues may be sporadically reported in popular media, it is often difficult to obtain a true understanding of authentic Chinese behaviors and practices. One such study area delves into whether Chinese users utilize technology to socialize in the same ways as people from western societies. As no book currently exists to address issues concerning Chinese social networks, this book takes on that shortage and opportunity.